The Effects of a Modeling and Computational Thinking Professional Development Program on STEM Educators’ Perceptions toward Teaching Science and Engineering Practices - Blake C. Colclasure; Tessa Durham Brooks; Tomáš Helikar; Scott J. King; Audrey Webb (Education Sciences, 2022)
Teachers’ integration of the Next Generation Science Standards and corresponding Science and Engineering Practices (SEPs) illustrate current science education reform in the United States. Effective teacher professional development (PD) on SEPs is essential for reform success. In this study, we evaluated the Nebraska STEM Education Conference, a PD program for middle school, high school, and first- and second-year post-secondary STEM teachers. This SEP-oriented PD program focused predominantly on the SEPs ‘developing and using models’ and ‘using mathematics and computational thinking.’ An electronic survey was used to measure participants’ (n = 45) prior integration of SEPs, influential factors and barriers to using SEPs, and changes to interest and confidence in using SEPs as a result of attending the PD program. Our results showed that teachers had limited prior use of SEPs in their teaching. Student interest and learning outcomes were the factors found to be most influential to teachers’ use of SEPs, while limited knowledge, confidence, and resources were the most commonly identified barriers. As a result of attending the PD program, participants significantly improved their confidence and interest to incorporate SEPs. We recommend continued SEP-oriented PD to foster successful NGSS integration and to advance reforms in science education.